Identification of Drought Tolerant Mechanisms in Maize Seedlings Based on Transcriptome Analysis of Recombination Inbred Lines - Min, Haowei; Chen, Chengxuan; Wei, Shaowei; Shang, Xiaoling; Sun, Meiyun; Xia, Ran; Liu, Xiangguo; Hao, Dongyun; Chen, Huabang; Xie, Qi (Frontiers in Plant Science, 2016)
Zea mays is an important crop that is sensitive to drought stress, but survival rates and growth status remain strong in some drought-tolerant lines under stress conditions. Under drought conditions, many biological processes, such as photosynthesis, carbohydrate metabolism and energy metabolism, are suppressed, while little is known about how the transcripts of genes respond to drought stress in the genome-wide rang in the seedling stage. In our study, the transcriptome profiles of two maize recombination inbred lines (drought-tolerant RIL70 and drought-sensitive RIL93) were analyzed at different drought stages to elucidate the dynamic mechanisms underlying drought tolerance in maize seedlings during drought conditions. Different numbers of differentially expressed genes presented in the different stages of drought stress in the two RILs, for the numbers of RIL93 Vs RIL70 were: 9 Vs 358, 477 Vs 103 and 5207 Vs 152 respectively in DT1, DT2 and DT5. Gene Ontology enrichment analysis revealed that in the initial drought-stressed stage, the primary differentially expressed genes involved in cell wall biosynthesis and transmembrane transport biological processes were overrepresented in RIL70 compared to RIL93. On the contrary, differentially expressed genes profiles presented at 2 day- and 5 day-treatments, the primary differentially expressed genes involved in response to stress, protein folding, oxidation-reduction, photosynthesis and carbohydrate metabolism, were overrepresented in RIL93 compared to RIL70. In addition, the transcription of genes encoding key members of the cell cycle and cell division processes were blocked, but ABA- and programmed cell death-related processes responded positively in RIL93. In contrast, the expression of cell cycle genes, ABA- and programmed cell death-related genes was relatively stable in RIL70. The results we obtained supported the working hypothesis that signaling events associated with turgor homeostasis, as established by cell wall biosynthesis regulation- and aquaporin-related genes, responded early in RIL70, which led to more efficient detoxification signaling (response to stress, protein folding, oxidation-reduction) during drought stress. This energy saving response at the early stages of drought should facilitate more cell activity under stress conditions and result in drought tolerance in RIL70.